Assessment of primary school students' decision-making related to tactical contexts - David Guitiérrez; Luis Miguel García-López (Springer, 2012)
<!-- /* Font Definitions */ @font-face {font-family:Times; panose-1:2 0 5 0 0 0 0 0 0 0; mso-font-charset:0; mso-generic-font-family:auto; mso-font-pitch:variable; mso-font-signature:3 0 0 0 1 0;} @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:auto; mso-font-pitch:variable; mso-font-signature:-536870145 1107305727 0 0 415 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; line-height:12.0pt; mso-line-height-rule:exactly; mso-pagination:widow-orphan; font-size:10.0pt; mso-bidi-font-size:12.0pt; font-family:Times; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; mso-ansi-language:EN-GB; mso-fareast-language:EN-US;} p.AbstractText, li.AbstractText, div.AbstractText {mso-style-name:"Abstract Text"; mso-style-unhide:no; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:justify; line-height:11.0pt; mso-line-height-rule:exactly; mso-pagination:widow-orphan; font-size:8.0pt; mso-bidi-font-size:10.0pt; font-family:Helvetica; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; mso-ansi-language:EN-US; mso-fareast-language:EN-US;} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; mso-ansi-language:ES; mso-fareast-language:EN-US;} @page WordSection1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.WordSection1 {page:WordSection1;} --> The purpose of this study was to assess and understand prior tactical knowledge and game performance as well as the relationship between the different components of game performance in invasion games. The participants (N = 22; girls: 13; boys: 9) were Physical Education students (ages: 11-12) with a low expertise in invasion games (they were selected among those with no other background in invasion games than PE lessons). Their game performance was videotaped, after which measures of motor execution and cognitive components were developed from observational analysis. Decision- making was measured on two levels: a) decision-making restricted to the performance of technical-tactical skills; and b) decision-making focused on adapting to the offensive tactical contexts of the game. Participants played an eight-minute-long 4-versus-4 generic invasion game. The latter was designed to meet both developmental needs and previous learning, so interference between motor execution ability and decision-making performance was minimized. The findings revealed that these students already had a basic concept of offensive and defensive game situations, both on-the-ball and off-the-ball. No significant differences were found between players' performance in penetrating-the-defense contexts and in those where they kept ball possession. The findings additionally highlighted the existence of significant relationships between decision-making and skill execution in getting open, tackling, marking off-ball and double teaming. Other links between game performance components are discussed throughout the paper. The importance of assessing game performance taking into account tactical contexts is also supported (Gutiérrez, González, García-López, & Mitchell, 2011), as well as some of the GCA pedagogical principles, e.g. the use of modified games (Oslin & Mitchell, 2006).